Analisis Pengaruh Parameter Operasi Terhadap Efisiensi Isentropik Turbin pada Pembangkit Listrik Tenaga Panas Bumi (PLTP) - Nurkhopipah, Siti; Endriansyah, Bagus (SURYA TEKNIKA, 2026)
Geothermal Power Plants (PLTP) utilize thermal fluids to drive steam turbines, where the isentropic efficiency of the turbine serves as a primary indicator of system performance. This study aims to analyze the influence of operating parameters on the isentropic efficiency of a steam turbine at PLTP Kamojang by comparing design and actual conditions. The research methodology includes primary data collection through field observations, linear regression analysis, and validation using the Root Sum Square (RSS) uncertainty analysis method. The results indicate that while the design isentropic efficiency reached 89.91%, the actual efficiency during the December 2024 period only achieved 76.93%, representing a performance degradation of 12.98%. Statistical analysis reveals that the steam mass laju alir massa is the most dominant parameter affecting efficiency decline, with a correlation coefficient (R) of 0.8993. Uncertainty analysis yielded a threshold of ±2.29%, confirming that the observed efficiency drop is scientifically significant and beyond the limits of instrumental error. This degradation is triggered by off-design operating conditions and potential physical issues such as fouling on turbine blades. This study is expected to serve as a basis for optimizing maintenance strategies and enhancing turbine performance to support more efficient and sustainable geothermal energy utilization.